As orquestras invadem as salas de estar: redefinição dos padrões e espaços para a escuta musical no Rio de Janeiro (1926-1931) - Emídio, Luiz Felipe Sousa Tavares (2010)
In the late nineteenth and early twentieth century, a series of technical innovations have been commercially and widespread on some urban groups everyday, in Brazil. Some of these technological innovations have played an important role in large-scale distribution of artistic works, which until then had an extremely limited potential for diffusion. Development of devices that can record and play music has been mechanically inserted into this logic, while the gramophones, phonographs, cylinders and discs became popular. By this time a new moment for production and consumption of music had started. Especially since the begging of electrical system for registration and production of sounds, this process bought important meaning to the way some peoples in Rio would leasing and sense music, besides it had contributed substantially to changes in the spatial references of these individuals